Synergistic antimalarial treatment of Plasmodium berghei infection in mice with dihydroartemisinin and Gymnema inodorum leaf extract - Sakaewan Ounjaijean; Voravuth Somsak (BMC, 2023)
Abstract Background Chemotherapy is crucial in the fight against malaria. The rise of resistance to most antimalarial medicines has been a serious hurdle to effective treatment. Artemisinin-based combination therapies (ACTs) are currently the most effective antimalarial medication. Malaria parasites are growing more resistant to ACTs, particularly in Southeast Asia. As a result, effective alternative antimalarials are in high demand. The leaf extract of Gymnema inodorum (GIE) has previously shown promise as an effective antimalarial. Therefore, this study evaluated the antimalarial potential of combination dihydroartemisinin (DHA) and GIE therapy against Plasmodium berghei in a mouse model. Methods The medications were evaluated using the standard 4-day test for determining the 50% effective dosage (ED50) of DHA and GIE on P. berghei ANKA (PbANKA). DHA and GIE were combined using a fixed-ratio approach, with DHA/GIE ED50s of 100/0, 80/20, 60/40, 40/60, 20/80, and 0/100, respectively. Results The ED50 against PbANKA was determined to be 2 mg/kg of DHA and 100 mg/kg of GIE. The 60/40 (DHA/GIE) ratio demonstrated significantly higher antimalarial activity than the other ratios (p < 0.001) against PbANKA, with 88.95% inhibition, suggesting synergistic efficacy (combination index (CI) = 0.68695). Furthermore, this ratio protected PbANKA-infected mice against loss of body weight and packed cell volume decline, leading to a longer survival time over 30 days. Conclusion Our results suggest that GIE could be an effective adjuvant to DHA that can enhance the antimalarial effects in the treatment of PbANKA-infected mice.